1991
DOI: 10.2527/1991.6983144x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of performance-tested boars using a single-trait animal model.

Abstract: Data structure designs for breeding value estimation of performance-tested boars using mixed-model methodology were compared. Computer models were based on estimates of parameters from the literature and from results of a survey of test station managers. Results were compared using accuracy (the correlation of true and estimated breeding values) and prediction error variance (PEV). The single-trait animal model included a fixed effect due to station-season, a random effect due to breeding value for ADG or back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Wood et al (1991) compared the effectiveness of different breeding programs for evaluation of pigs in test stations, using only the diagonal elements of the PEV matrix to measure connectedness. Foulley et al (1992) proposed calculating the ratio of the determinants of PEV matrices with and without management unit (e.g., TG) in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Wood et al (1991) compared the effectiveness of different breeding programs for evaluation of pigs in test stations, using only the diagonal elements of the PEV matrix to measure connectedness. Foulley et al (1992) proposed calculating the ratio of the determinants of PEV matrices with and without management unit (e.g., TG) in the model.…”
Section: Discussionmentioning
confidence: 99%
“…If the size of herd was relatively small (less than 100), the improvement of genetic gain might be clearer because the likelihood of producing extreme individuals was small in those cases (Wood, 1991). Maraei (1993) showed that the larger the genetic mean difference between herds, the more the genetic gains increased at the first time of their connection.…”
Section: The Effects Of Bias On Genetic Response To Selectionmentioning
confidence: 99%